Relevansi Nilai Informasi Akuntansi dan Keuangan dalam Pengembalian Saham: Kasus Bank Komersial Indonesia (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study examines the relevance of accounting and financial information in explaining stock returns of commercial banks listed on the Indonesia Stock Exchange (IDX) from 2014 to 2024. The independent variables include Earnings Per Share (EPS), Book Value Per Share (BVPS), Dividend Payout Ratio (DPR), and bank size (total assets), with stock return as the dependent variable. The analysis employs panel data regression with a Random Effect Model and classical assumption testing.The results indicate that only DPR significantly affects stock returns (β = -0.077; p < 0.05), showing a negative relationship. In contrast, EPS, BVPS, and bank size were statistically insignificant (p > 0.05). The low coefficient of determination (R² = 7.6%) suggests that most variations in stock returns are driven by external factors, such as macroeconomic conditions or monetary policies.These findings imply that accounting information has limited relevance in predicting stock returns in Indonesia’s banking sector. Investors should consider non-financial and external factors, while bank management should balance dividend policies with long-term growth strategies.